Meninjau Tafsir Al-Jami’ Li Ahkami Al-Qur’an Karya Imam Al-Qurthubi: Manhaj dan Rasionalitas - Muhammad Rifaldi; Muhammad Sofian Hadi (Jurnal Iman dan Spiritualitas, 2021)
One of the hardest things apart from a mufassir when interpreting the Qur'an is mazhab's fanaticism, but al-Qurtubi can point out that it can be overcome. This led to the study's being done, the purpose of the study was to uncover public methodology and typical methodology (manhaj) al-Imam al-Qurtubi in his interpretation. Besides, it was also meant to look at a correlation of his written interpretation of al-Qurtubi with manhaj tafsir that it did. The study is also trying to describe the effect of philosophical thinking on the interpretation of al-Qurtubi, since fiqh is an Islamic science based on proper and rational thinking. To achieve these objectives, the methods used are descriptive analysis and book research, so the study counts as qualitative research. The data used is qualitative, either primary or secondary data. The study resulted in several findings, i.e., al-Qurtubi applied a precise interpretation methodology, both types of interpretive source, the tahlili interpretation method, and the fiqh approach in each text considered; at least five manhaj interpretations indicated by al-Qurtubi; and  al-Qurtubi also employed a method of rational thought in its interpretation, which is shown by the results of induced thinking and the similarity of the objectives between manhaj tafsir and philosophy.